From OAU To AFCTA - Analysing The Prospects For Economic Development In Africa - Nagu, Yakubu Idisire (Department of Commercial Law, 2020)
On the 21st March 2018, leaders from across the African continent met at an extraordinary summit of the African Union (AU) in Kigali, Rwanda to sign a deal for the formation of an African continental free trade area (AfCFTA). This step is perhaps the biggest leap towards the age-long dream of cross-border economic integration on the African continent since the formation of the Organisation of African Unity (OAU) in 1963. With the continent’s population expected to hit the two billion mark in 2050, it seems the pact could not have come at a better time. Africa, the subject of the agreement, consists of fifty- five States which collectively, is a 1.2 billion people large market however possessing a joint GDP of only $2.5 trillion dollars. If negotiations are concluded, the African continent would have succeeded in the creation of the largest free trade area since the Marrakesh agreement which led to the WTO governed multilateral trading system. Today the top trading partners of African Union member States are non-African countries. Only twenty per cent of Africa’s total trade is with its continental neighbours, whereas an estimated eighty per cent of its trade is with other trading partners across the world. The African continental free trade initiative aims to shift the trade paradigm in this regard, in a way that will increase the region’s share of its internal trade and consequently lead to growth and development. It is against this background that this work assesses the prospects of the new African Continental Free Trade Area (AfCFTA) towards meeting the goal of continental development. This research argues that the development integration approach is the most suitable option for the attainment of the ambitious goals of the initiative. In particular, the work explores the ways in which the new AfCFTA can manage the asymmetrical developmental needs of various African States. The research also assesses the dispute settlement mechanisms which are necessary to resolve friction which may arise as deeper levels of integration are attained.